Identification of biochemical biomarkers associated with premature cervical shortening in high-risk, asymptomatic pregnant women: a retrospective data analysis - Lauren Di Salvo; Thomas Cade; Penelope Sheehan; Harry M. Georgiou; Megan Di Quinzio; Shaun P. Brennecke (Taylor & Francis Group, 2023)
Reliably predicting spontaneous preterm birth remains challenging, therefore it persists as a major contributor to perinatal morbidity and mortality. The use of biomarkers to predict premature cervical shortening, a recognised risk factor for spontaneous preterm birth, is yet to be fully explored in current literature. This study evaluates seven cervicovaginal biochemical biomarkers as possible predictors of premature cervical shortening. Asymptomatic, high-risk women (n = 131) presenting to a specialised preterm birth prevention clinic were analysed through a retrospective data analysis. Cervicovaginal biochemical biomarker concentrations were obtained, and the shortest cervical length measurement, up to 28 weeks' gestation, was recorded. Associations between biomarker concentration and cervical length were then analysed. Of the seven biochemical biomarkers, Interleukin-1 Receptor Antagonist and Extracellular Matrix Protein-1 had statistically significant relationships with cervical shortening below 25 mm. Further investigation is required to validate these findings and any downstream clinical utility, with intentions to improve perinatal outcomes.IMPACT STATEMENT What is already known on this subject? Preterm birth is a major cause of perinatal morbidity and mortality. A woman's risk of delivering preterm is currently stratified using historical risk factors, mid-gestation cervical length, and biochemical biomarkers such as foetal fibronectin. What do the results of this study add? In a cohort of high-risk, asymptomatic pregnant women, two cervicovaginal biochemical biomarkers, Interleukin-1 Receptor Antagonist and Extracellular Matrix Protein-1, displayed associations with premature cervical shortening. What are the implications of these findings for clinical practice and/or further research? Further investigation into the possible clinical utility of these biochemical biomarkers is warranted, with a view to improving preterm birth prediction and antenatal resource utilisation, thereby reducing the burden of preterm birth and its sequelae in a cost-effective manner.